2016
DOI: 10.1038/ajg.2016.297
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Pancreas Fluid Collection: Methods and Relevance for Clinical Care and Translational Science

Abstract: Pancreatic secretions have an important role in the regulation of a normal nutritional state but can be altered owing to a variety of pathophysiological mechanisms in the context of exocrine pancreatic disease. The development of an endoscopic technique for collection of pancreatic fluid, termed endoscopic pancreatic function testing, has led to improved understanding of these alterations and is particularly helpful to characterize chronic pancreatitis. In addition, investigators have found endoscopically coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 48 publications
0
25
0
3
Order By: Relevance
“…There are currently no clinically validated and utilized markers of fibrosis and inflammation in pancreatic fluid although preliminary studies have demonstrated that this fluid can be used for a variety of measures related to inflammation and fibrosis [109]. In near future, it may be possible that studies of pancreatic fluid can lead to biomarkers of inflammation and fibrosis that characterize subsets of patients and response to specific therapeutic interventions.…”
Section: Diagnosis Of Chronic Pancreatitismentioning
confidence: 99%
“…There are currently no clinically validated and utilized markers of fibrosis and inflammation in pancreatic fluid although preliminary studies have demonstrated that this fluid can be used for a variety of measures related to inflammation and fibrosis [109]. In near future, it may be possible that studies of pancreatic fluid can lead to biomarkers of inflammation and fibrosis that characterize subsets of patients and response to specific therapeutic interventions.…”
Section: Diagnosis Of Chronic Pancreatitismentioning
confidence: 99%
“…Of those with positive sPFTs, 9 later developed CP where as of the 70 with negative sPFTs, only 2 patients later developed chronic pancreatitis 30 . Sensitivity & specificity of diagnosing CP with sPFTs were 82% and 86%, respectively whereas the PPV and NPV were 45% and 97%, respectively 30 . This suggests primary utility of secretin-stiumlated PFT lies in ruling out CP in patients who present with signs & symptoms concerning for CP, such as chronic abdominal pain.…”
Section: Imaging For Chronic Pancreatitismentioning
confidence: 94%
“…Direct PFTs allow for evaluation of both acinar and ductal pancreatic cells by aspirating duodenal contents after stimulation by either CCK or secretin, respectively 30 . When stimulated by CCK, pancreatic enzymes are measured in the duodenal contents, and bicarbonate concentration is measured from the fluid following secretin stimulation.…”
Section: Imaging For Chronic Pancreatitismentioning
confidence: 99%
See 2 more Smart Citations